Self-tuning PID controller for active suspension system with hydraulic actuator - Mat Hussin, Ab. Talib (2013)
This paper investigated the performance of PID controller for active suspension system. A half car model has been simulated by using an analytical model within Matlab SIMULINK environment. Three different road disturbances, namely, the bump and hole, sine and random input have been applied to disturb the suspension system. Based on these three road disturbances, the performances of passive and active suspension system were investigated. Moreover, for active suspension system, hydraulic actuator was included in the simulation and PID controller was introduced. Three tuning methods namely heuristic tuning, Ziegler-Nichols (ZN) tuning, and iterative learning algorithm (ILA) were used to obtain the optimum value of the PID controller parameters. A comparative study was carried out between active and passive suspension systems, and these three methods of tuning the PID controller. The active suspension system has been proven to perform better than the passive suspension system provided the PID controller parameters are tuned properly. Also, in this investigation, the comparative assessment indicated that the PID controller tuned by the iterative learning algorithm for active suspension system with hydraulic actuator has performed better than the other two tuning algorithms.